Enzymatic biosynthesis and immobilization of polyprotein verified at the single-molecule level - Deng, Yibing (2019)
The recent development of chemical and bio-conjugation techniques allows for the engineering of various protein polymers. However, most of the polymerization process is difficult to control. To meet this challenge, we develop an enzymatic procedure to build polyprotein using the combination of a strict protein ligase OaAEP1 (Oldenlandia affinis asparaginyl endopeptidases 1) and a protease TEV (tobacco etch virus). We firstly demonstrate the use of OaAEP1-alone to build a sequence-uncontrolled ubiquitin polyprotein and covalently immobilize the coupled protein on the surface. Then, we construct a poly-metalloprotein, rubredoxin, from the purified monomer. Lastly, we show the feasibility of synthesizing protein polymers with rationally-controlled sequences by the synergy of the ligase and protease, which are verified by protein unfolding using atomic force microscopy-based single-molecule force spectroscopy (AFM-SMFS). Thus, this study provides a strategy for polyprotein engineering and immobilization.